Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd006573.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral prophylactic intervention for chronic hepatitis C virus in patients undergoing liver transplantation

Abstract: There is currently no evidence to recommend prophylactic antiviral treatment to prevent recurrence of HCV infection either in primary liver transplantation or re-transplantation. Further randomised clinical trials with adequate trial methodology and adequate duration of follow-up are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…HCV antibody therapy starts in the anhepatic phase and then is continued for 12 to 14 wk after transplant. Three trials [110][111][112] comparing high dose HCV antibody vs. low dose HCV antibody were included in a Cochrane meta-analysis [113] . There was no difference in patient and graft survival, virological response or fibrosis on histology.…”
Section: Post-transplant Antiviral Treatmentmentioning
confidence: 99%
“…HCV antibody therapy starts in the anhepatic phase and then is continued for 12 to 14 wk after transplant. Three trials [110][111][112] comparing high dose HCV antibody vs. low dose HCV antibody were included in a Cochrane meta-analysis [113] . There was no difference in patient and graft survival, virological response or fibrosis on histology.…”
Section: Post-transplant Antiviral Treatmentmentioning
confidence: 99%
“…Therefore, the results were also very different, with SVR rates ranging 0% to 56% (median: 33%), discontinuation rates ranging 4% to 58%, and dose reduction rate ranging 28% to 100%. In addition, the survival benefit of the treatment has not been confirmed in most studies so far, and it is compelling to conclude that there is currently no evidence to support the antiviral treatment for recurrent graft hepatitis C due to the lack of clinical benefit and frequent adverse effects, as concluded by the recent Cochrane meta-analysis [191]. On the other hand, recent retrospective cohort studies with a considerable follow-up duration found improved patient/graft survival in patients who obtained an SVR after antiviral treatment [35, 192194].…”
Section: Antiviral Treatmentmentioning
confidence: 99%
“…The rate of recurrence of HBV fell dramatically because of the introduction of human HBV immunoglobulins and nucleoside analogs 9. Although some antiviral agents, such as ribavirin or interferon, have been used as prophylactic therapy to prevent HCV infection in liver grafts, it is not clear whether these agents are of any benefit to patients 10,11. The response to antiviral therapies may contribute to the causal difference in late allograft dysfunction between the HBV and HCV.…”
Section: Discussionmentioning
confidence: 99%